2010
DOI: 10.1002/pip.1045
|View full text |Cite
|
Sign up to set email alerts
|

Silicon quantum dot based solar cells: addressing the issues of doping, voltage and current transport

Abstract: Silicon quantum dot (Si QD) solar cells offer the potential to tune the effective band gap through quantum confinement and hence allow fabrication of optimised tandem devices in one growth run in a thin film process. Previous work in our group has shown how such cells can be fabricated by sputtering of thin layers of silicon rich oxide sandwiched between a stoichiometric oxide that on annealing crystallise to form Si QDs of uniform and controllable size. Doping multilayers with P and B allows formation of a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 25 publications
0
41
1
Order By: Relevance
“…40,59 Therefore, to compensate such deviations, we have applied a correction of 2.0 eV to VBO and HB values, and of -0.8 eV to CBO and EB values, while leaving E g unchanged. Since our QD size range is small, we apply the same correction for all the samples.…”
Section: Structures and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…40,59 Therefore, to compensate such deviations, we have applied a correction of 2.0 eV to VBO and HB values, and of -0.8 eV to CBO and EB values, while leaving E g unchanged. Since our QD size range is small, we apply the same correction for all the samples.…”
Section: Structures and Methodsmentioning
confidence: 99%
“…Most of the available studies on single-and two-QDs have been performed by using nonequilibrium Green functions formalism (NEGFF) with constant transition rates between QDs and one energy level per QD [31][32][33][34][35][36] , and by using tunneling transmission coefficients with planar Si/SiO 2 values for the barrier height, and bulk-Si band gap. [37][38][39][40] Here we make use of a different approach, 41-43 based on the transfer Hamiltonian formalism and non-coherent rate equations to describe the current, that takes into account the local potential due to the QD charge, com-V FIG. 1.…”
Section: Structures and Methodsmentioning
confidence: 99%
“…Impurity doping of Si QDs is still not well understood as the doping mechanism is more complex than in c-Si [8]. Doping can drastically alter the structural, electrical and optical properties of the Si QDs themselves.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental investigations have shown that the material possesses better nanocrystal growth and carrier transport properties [8]. However, few studies have been conducted to comprehensively examine the new material's optical characteristics, which are essential in the understanding of device operation.…”
Section: Introductionmentioning
confidence: 99%